Odpowiedzi

2010-03-30T19:05:44+02:00
A) -6-24+3+4=-23
b)8-8+0,5-1-4+1=-3,5
c)27-21+2-12-21=-25
1 5 1
2010-03-30T19:09:04+02:00
A) -6 + 8*(-3) - (-3) - 2*(-2) = -6 - 24 + 3 + 4 = -23
b) -8*(-1) - 4*2 + 0,5 - (-1) - 2*2 + 1 = 8 - 8 + 0,5 + 1 - 4 = -2,5
c) 9*3 - (7*3 + (-2)) + (6*(-2) - 7*3) = 27 - (21 - 2) + (-12 - 21) = 27 - 19 + (-33) = -25
1 5 1
2010-03-30T19:09:20+02:00
A) -y+8z-z-2x= .. dla: x = -2 , y= 6, z = -3
-y + 8z - z - 2x = -6 + 8*(-3) - (-3) - 2*(-2) = -6 - 24 + 3 + 4 = -23

b)-8y-4z+x-y-2z+1 = .. dla: x= 0,5, y= -1, z =2
-8y - 4z + x - y - 2z + 1 = -8*(-1) - 4*2 + 0,5 - (-1) - 2*2 + 1 =
=8 - 8 + 0,5 + 1 - 4 + 1 = - 1,5

c) 9y-(7y+x) + ( 6x - 7y) = .. dla: x = -2, y =3
9y - (7y + x) + (6x - 7y) = 9*3 - [7*3 + (-2)] + [6*(-2) - 7*3] =
27 - [21 - 2] + [ -12 - 21] = 27 - 19 + (-33) = -25